Investment‐Based Corporate Bond Pricing - KUEHN, LARS‐ALEXANDER; SCHMID, LUKAS (Journal of Finance, 2014)
ABSTRACT A standard assumption of structural models of default is that firms' assets evolve exogenously. In this paper, we examine the importance of accounting for investment options in models of credit risk. In the presence of financing and investment frictions, firm‐level variables that proxy for asset composition are significant determinants of credit spreads beyond leverage and asset volatility, because they capture the systematic risk of firms' assets. Cross‐sectional studies of credit spreads that fail to control for the interdependence of leverage and investment decisions are unlikely to be very informative. Such frictions also give rise to a realistic term structure of credit spreads in a production economy.